Lead hexacyanoferrate(II) tetrahydrate: Crystal structure, FTIR spectroscopy and thermal decomposition studies - Gil, Diego Mauricio (2012)
Pb2[Fe(CN)6]4H2O was synthesized by mixing aqueous solutions of lead(II) nitrate and potassium ferrocyanide. Its crystal structure was solved ab initio from synchrotron powder X-ray diffraction data using the direct methods and refined by the Rietveld method. Thermal analysis (TGA and DTA), Fourier Transform Infrared Spectroscopy (FTIR) and scanning electron microscopy (SEM) studies were also used for the solid state characterization of this compound and its decomposition products. The complex crystallizes in the monoclinic crystal system, space group P21/n. The Fe2+ cation is octahedrally coordinated to six cyano groups, and the Pb2+ cation is penta-fold coordinated to three N atoms from C„N ligands and two O atoms from coordinated water molecules. The most important peculiarity of the structure of this complex is the occurrence of water bridges linking two neighboring Pb2+ cations. An unusual Fe–C„N–Pb(H2O)2– Pb–N„C–Fe linkage alternates with a usual Pb–N„C–Fe one. Zeolitic water molecules are also observed in the structure; they are located in small channels in the structure and they are hydrogen bonded to coordinated water molecules forming a cumulus. Coordinated water and zeolitic water molecules in this complex can be removed without affecting the hexacyanometallate framework. The thermal decomposition in air to produce Pb2Fe2O5 and PbO as final products has been studied by thermogravimetric and differential thermal analysis, FTIR spectroscopy and laboratory powder X-ray diffraction. The crystallite size and morphology of the complex and its thermal decomposition products were evaluated by SEM.